PENINGKATAN LITERASI SAINS MELALUI PENGEMBANGAN MEDIA BIG BOOK - Ikbal, Ikbal (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
This research is a level 3 research and development (R&D) which aims to develop existing products. The product developed is the big book learning media which is then used as a means to improve the literacy science of students at MIN Bone. This research adopts Borg and Gall development research steps which include research and information gathering, planning, initial product development, conducting initial testing by media/design experts, material/content experts and learning practitioners, product revisions, conducting field trials, revisions the final product. There are three data collection techniques used in this study, namely validation carried out by the validator, effectiveness obtained through increasing literacy science and student responses to learning media. The results of the big book media validity test conducted by media/design experts are 85% with good qualifications, material/content experts are 91% with very good qualifications and learning practitioners are 91% with very good qualifications. The effectiveness of the big book media in improving literacy science. through the N-Gain 32 test which got a score of (g) 0.7 as many as 2 Â students, a value of 0.7 (g) 0.3 as many as 31 students, a value of (g) 0 ,3 as many as 2 Â students. The student response to the attractiveness of the big book media is 91% with very good qualifications.